APLIKASI SISTEM PAKAR UNTUK IDENTIFIKASI TINGKAT PENCEMARAN LIMBAH CAIR DOMESTIK BERBASIS MOBILE ANDROID - Oktianti Dwi Pratiwi; Ina Agustina; Ucuk Darusalam (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2016)
The area is the largest source of the presence of domestic wastewater as well as being the largest contributor to environmental pollution. To help minimize the problems that occurred required an intelligent system design is to adopt an expert knowledge into an application. ILCIdroid application designed to identify the level of pollution from domestic wastewater on android based mobile devices. Application of expert system is designed using the Eclipse IDE tools and Matlab toolbox. To determine the results of the identification, use the rules of the rules established by the fuzzy logic based on the data obtained, which then conducted a search of data tracking the fore or forward chainning. The test results show the output generated by the matlab application has the appropriate conclusion.